Characterization of the colostrum proteome of primiparous Holstein cows and its association with colostrum immunoglobulin G concentrations - Ezequias Castillo-Lopez; Patrick Biber; Arife Sener-Aydemir; Karin Hummel; Ebrahim Razzazi-Fazeli; Nicole Reisinger; Qendrim Zebeli; Susanne Kreuzer-Redmer; Thomas Hartinger (Journal of Animal Science and Biotechnology)
Abstract Background The objective was to characterize the colostrum proteome of primiparous Holstein cows in association with immunoglobulin G (IgG) content. Immediately after calving, colostrum samples were collected from 18 cows to measure IgG concentration. Based on colostrum IgG content, samples were classified through cluster analysis and were identified as poor, average, and excellent quality. The proteome was assessed with quantitative shotgun proteomics; abundance data were compared among the colostrum types; enrichment analysis of metabolic processes and proteins classes was performed as well. We also tested correlations between this proteome and blood globulin level of cows and passive immunity level of calves. Results On average, 428 proteins were identified per sample, which belonged mainly to cellular process, biological regulation, response to stimulus, metabolic process, and immune system process. Most abundant proteins were complement C3 (Q2UVX4), alpha-S1-casein (P02662), Ig-like domain-containing protein (A0A3Q1M032), albumin (A0A140T897), polymeric immunoglobulin receptor (P81265), lactotransferrrin (P24627), and IGHG1*01 (X16701_4). Colostrum of excellent quality had greater (P < 0.05) abundance of serpin A3-7 (A2I7N3), complement factor I (A0A3Q1MIF4), lipocalin/cytosolic fatty-acid binding domain-containing protein (A0A3Q1MRQ2), complement C3 (E1B805), complement component 4 binding protein alpha (A0AAF6ZHP5), and complement component C6 (F1MM86). However, colostrum of excellent quality had lower (P < 0.05) abundance of HGF activator (E1BCW0), alpha-S1-casein (P02662), and xanthine dehydrogenase/oxidase (P80457). This resulted in enrichment of the biological processes predominantly for complement activation alternative pathway, complement activation, complement activation classical pathway, humoral immune response, leukocyte mediated immunity, and negative regulation of endopeptidase activity in excellent-quality colostrum. Additionally, some colostrum proteins were found to be correlated with the blood globulin level of cows and with the passive immunity level of calves (P < 0.05; r ≥ 0.57). Conclusions This study provides new insights into the bovine colostrum proteome, demonstrating associations between IgG levels and the abundance of other proteins, as well as the enrichment of metabolic processes related to innate immune response. Thus, results suggest that the colostrum proteomic profile is associated with the content of IgG. Future research should deeply explore the association of these findings with pre-calving nutrition status and blood composition of the cow, and with passive immunity transfer to the calf.